Reliability of testicular stiffness measurement by shear wave elastography to predict testicular atrophy in patients with chronic liver disease - Sahin, Tuna; Ertekin, Ersen; Gok, Mustafa; Kandemir, Altay; Ture, Mevlut (Annals of Medical Research, 2021)
Aim: Chronic liver disease is one of the most important public health problems in both developed and developing countries. It has been reported that testicular atrophy may occur in these patients. The aim of this study is to demonstrate changes in testicular structure and elasticity due to hypogonadism secondary to chronic liver disease (CLD) by shear wave elastography (SWE).Material and Methods: Eighteen patients aged 22-50 years were included in the study. The control group consisted of 16 participants aged 17-52 years. In all patients and in the control group; first scrotal gray scale and doppler US examination were performed to determine the presence of focal lesions and structural anomalies in both testicles, then the mean testicular shear wave velocity values (SWVV) in the parenchyma was calculated. Testicular volumes and testicular arterial flow indices (Vmax, RI) were recorded. Results: The results of 34 participants (patient and control groups) were examined; There was no significant difference between volumetric measurements, flow indices and SWVQ values between the two groups. In addition, right testicular arterial Vmax values were lower in the patient group than in the control group (p 0.005). Conclusion: A decrease in right testicular arterial Vmax indicates that CLD may play an acceptable role in the development of testicular atrophy. However, the duration of the disease and the drugs used can have an impact on our findings. Prospective studies with larger cohorts may be useful in revealing this relationship.